2022
DOI: 10.1101/2022.09.28.509853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transcriptional landscape of glycosylation-related genes in cancer

Abstract: Changes in glycosylation patterns have been associated with malignant transformation and clinical outcome in several types of cancer, although no comprehensive analysis has been performed in a pan-cancer setting. Here, we performed an extensive transcriptomic analysis of glycosylation related genes (such as enzymes involved in synthesis and degradation of glycoconjugates, transporters, mucins and galectins), using publicly available bulk and single cell transcriptomic data sets from tumor samples and cancer ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In addition, ST3GAL4 is related to an increased invasive phenotype in tumor cells as it generates the glycan sialyl-Lewis X, which facilitates cell adhesion 72,73 . Interestingly, recent studies also observed increased ST3GAL4 expression in the stroma in other cancer types, including colorectal, lung, cervical and esophageal cancer 67,74 . Stromal sialylation therefore likely plays a role in other cancer types as well.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, ST3GAL4 is related to an increased invasive phenotype in tumor cells as it generates the glycan sialyl-Lewis X, which facilitates cell adhesion 72,73 . Interestingly, recent studies also observed increased ST3GAL4 expression in the stroma in other cancer types, including colorectal, lung, cervical and esophageal cancer 67,74 . Stromal sialylation therefore likely plays a role in other cancer types as well.…”
Section: Discussionmentioning
confidence: 92%
“…For identification of CAF subtypes, cells were reclustered as described before but using a resolution of 0.25. The function AddModuleScore was employed to generate gene scores for different glycosylation pathways using genesets previously described 74 (supplementary Table 3). The scripts used in this manuscript for the analysis of scRNA-Seq can be found in https://github.com/MolecularCellBiologyImmunology/ Sialylation_CAF.…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…In conclusion, we demonstrate that the contribution of only ST3Gal5 on anti-tumor immunity is modest. Nevertheless, in combination with other sialyltransferases, the effect of glycan-dependent immune evasion might be larger, since it is not one single modification, but multiple glycosylation changes occurring in each tumor type ( Rodriguez et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%